"Mama Lima"; The significance of women’s role in protecting nature, nurture, and culture in Banda Islands - Farid, Muhammad; Sadée, Juul (Wacana, Journal of the Humanities of Indonesia, 2023)
The historiography of Banda has paid little attention to the existence of women. Stories involving women are mainly about romance, family, and suffering. In reality, the existence of “Mama Lima” (groups of five women) is very strong in the Banda tradition (adat). They are the carriers of knowledge and tradition, a consequence of matriarchy. They determine the content and implementation of adat ceremonies like Buka kampong, forming the set of social norms and customary law of the community. Mama Lima groups are a living example of women throughout the ages who have played a significant role in welfare, the environment, religion, spiritualism, education, and nature. This article discusses the position of women in Banda from its colonization in 1609: defending their land, customs, and descendants, to this day. The results show that Banda women have been practising gender equality for centuries, passing their functions on to the younger generation, and have become an example for all Bandanese today.